The Oxford history of the classical world - Boardman, John 1924- .; Griffin, Jasper; Murray, Oswyn (Oxford University Press, 1986)
Provides a historical framework of the Greco-Roman world focusing on the political and social history, literature, philosophy, the arts, etc.